Pembuatan Situs Web SMA Negeri 7 Nabire Menggunakan PHP dan MySQL: Making a Website for SMA Negeri 7 Nabire Using PHP and MySQL - Maulana, Muhamad Fijai; Naibaho, Julius Panda Putra (Universitas Papua, 2023)
In the current era of globalization, the existence of a network internet become a means to obtain information and also the delivery of information quickly. With a network internet can benefit its users both in individuals and institutions such as education, companies, state government and in commercial institutions. By using internet, an institution of government or educational institutions that can display profiles, data or information to the public through the network internet by utilizing the website facilities. The school profile information system as well as all information in schools is still done manually using banners or letters. Indirectly, this has become one of the obstacles in conveying information and also an obstacle in improving the quality of education at Nabire 7 State Senior High School. On this website, the process can also be carried out input, edit and delete data which can be done by admin so that it is available for those who want to know information about SMA Negeri 7 Nabire without having to come to school, and with a website These errors and mistakes in conveying information will be easier to fix through this website.